THE ECONOMIC AND SOCIAL STATUS OF WOMEN IN BAGHDAD (334-656 AH / 945-1258 AD). - Dosky, Remzyia Hussan (Journal of Duhok University, 2018)
The research seeks to determine the manifestation of women`s life in Baghdad from the economic and social aspects, it`s known that there is a close link (connection) between the economic and social aspects of human in general. Over the Islamic history women could maintain their economical status from deserve sources. Beside that the inheritance, dowry, gifts, and connections played an important role in the richness of women. The work has an important role in reinforcing the economical and social position of women, especially the encouraging of Islam to work because it's important to develop the person`s fortune, that didn’t deprive the women to exercise the works that they exercised before Islam, whether directly and personally or by agents, deputies and offices without obstacles like age, place and time. The luxury life in succession palaces led to the appearance of odalisques abnormally who strived for self-developing. The research concluded with results indicate to the legitimacy of these ways to develop the women`s status in the Islamic outlook and also showing the importance of work to develop the women`s fortune